2017
DOI: 10.1007/s00384-017-2910-9
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery for giant benign rectal tumours: is large size a contraindication?

Abstract: TEM is feasible and safe for the treatment of giant benign rectal tumours. It may be an alternative method for proctectomy in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
2
5
1
2
Order By: Relevance
“…Of note is the fact that our latest recurrence was caught at 16.9 months, however this patient did not have their first post-surgical endoscopic surveillance visit until 16.9 months, thus the recurrence may have been caught earlier had the patient been scoped at 6 and 12 months. Studies show similar recurrence rates ranging from 2.4%-10.5% as that seen in our adenoma patients 18,19 . A study by Barendse et al showed that in benign lesions excised by TEM, larger size (> 3 cm) was a significant factor for recurrence and the median time to recurrence was 10 months 23 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Of note is the fact that our latest recurrence was caught at 16.9 months, however this patient did not have their first post-surgical endoscopic surveillance visit until 16.9 months, thus the recurrence may have been caught earlier had the patient been scoped at 6 and 12 months. Studies show similar recurrence rates ranging from 2.4%-10.5% as that seen in our adenoma patients 18,19 . A study by Barendse et al showed that in benign lesions excised by TEM, larger size (> 3 cm) was a significant factor for recurrence and the median time to recurrence was 10 months 23 .…”
Section: Discussionsupporting
confidence: 87%
“…The focus of our study was on endoscopic surveillance practices post TEM and recurrence patterns in benign and malignant lesions, at our institution. The demographics of our patients, tumour characteristics, surgical results and outcomes are similar to other studies on TEM for benign and malignant lesions [17][18][19][20][21][22] . Although there is currently no established standardized protocol for endoscopic surveillance of patients post-TEM at our institution, the majority of the patients had their endoscopy within the timeframes of the commonly quoted surveillance recommendation from the clinic notes, namely every 6 months for 2 years.…”
Section: Discussionsupporting
confidence: 73%
“…Šios operacijos, kartu su vėlesnėmis įvairiomis transanalinėmis minimaliai invazyviomis metodikomis (TAMIS), endoskopine mukozektomija (EMR) ir endoskopine submukozine disekcija (ESD) [8] yra pagrindiniai tiesiosios žarnos polipų šalinimo būdai -priklausomai nuo ligoninės turimos įrangos ir patirties. Šie metodai leidžia polipus pašalinti vienu bloku, jei šalinama T1 karcinoma -toks gydymas gali būti pakankamas [9], tačiau gigantiniai, ypač cirkuliarūs, tiesiosios žarnos polipai yra tam tikras iššūkis. Viena vertus, patologija gerybinė, todėl pageidautinos mažai invazyvios, mažesnės apimties operacijos, kurios saugesnės pacientui, komplikacijos retos.…”
Section: Diskusijaunclassified
“…Gana dažnai polipai siekia rezekcinį kraštą -nuo 9,7 iki 30,7 proc. atvejų [9]. Atliekant viso sienos storio eksciziją, pašalinimas vienu bloku labiau tikėtinas, tačiau suartinti ir susiūti rezekcijos kraštus nenaudojant tempimo ne visada įmanoma, be to, didėja pilvaplėvės perforacijos rizika.…”
Section: Diskusijaunclassified
“…Transanal endoscopic microsurgery for a rectal polypa video vignette doi:10.1111/codi.15049 Dear Editor, Transanal endoscopic microsurgery (TEM) was first introduced in 1983 with the aim of providing better access to difficult rectal tumours [1]. Buess et al [2] described all the additional instrumentation needed for the procedure. Now TEM has the following indications: large endoscopically irremovable benign polyps (previously, we have shown that giant size is not a contraindication), tumours located 3 to 12 cm in the rectum and lesions occupying less than 40% of the circumference of the bowel lumen.…”
mentioning
confidence: 99%